Internalization of Moral Values of Santri Discussion in Bahtsul Masa'il at Fathul Ulum Islamic Boarding School Jombang - Qurrotul Ainiyah; Ali Mustofa (Institut Attanwir Bojonegoro, 2024)
Moral is an important thing so they need to be formed from an early age so that they become habitual and characteristic, including morals in deliberations which are widely studied and practiced by students in deliberations. One of the practices of the morals of deliberation is during the implementation of the Bahtsul Masa'i[1]l Book of Fiqh at the Fathul Ulum Islamic Boarding School in Jombang. The moral values ​​of students in deliberation are based on studies in the book Ta'lim al-Muta'alim by Sheikh Al Zarnuji, which also includes the Koran in deliberation. The process of internalizing moral values ​​in student deliberation activities in Islamic boarding schools goes through certain stages, steps and methods. The stages passed are Value Transformation, Value Transaction. and Transinternalization. The steps taken are listening, responding. Organization. And Characterization. Meanwhile, the method of internalizing moral values ​​in student deliberation activities that is applied is example and habituation.